(untitled) (Journal of actual problems of jurisprudence, 2018)
The article analyzes history of a definition «legal status of a child», specific features of children rights in Kazakh common law, reasons of contiguity of children rights associated with mother’s rights. The article calls attention to international regulation of children legal status as well. Key words: child, legal status, international legal regulation, national legislation, mechanism of children rights protection.